2019
DOI: 10.1016/j.scitotenv.2019.05.386
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of urban sustainability in Chinese resource-based cities: A panel quantile regression approach

Abstract: Improving energy efficiency and reducing environmental pollution emissions are two important ways to alleviate energy problems. Despite the progress in energy efficiency, the growth in energy demand still exceeds the efficiency improvements. This study adopts nonparametric methods to estimate the total factor energy efficiency (TFEE) of 105 resource-based cities covering the period 2010-2016 in China and analyzes the spatiotemporal characteristics of changes in energy efficiency. Furthermore, panel quantile re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 46 publications
1
51
0
1
Order By: Relevance
“…Among them, the growth rate of ECPC in Ningxia, Qinghai and Xinjiang was significantly higher than the national average, which might result from these provinces being exceptionally rich in petrochemical resources, and energy production is a pillar industry in these provinces. Therefore, ECPC of these provinces was affected to some extent, which was consistent with the research conclusions of Yan et al and Wu et al [56,57].…”
Section: Values Of Eiwb and Its Distributionsupporting
confidence: 90%
“…Among them, the growth rate of ECPC in Ningxia, Qinghai and Xinjiang was significantly higher than the national average, which might result from these provinces being exceptionally rich in petrochemical resources, and energy production is a pillar industry in these provinces. Therefore, ECPC of these provinces was affected to some extent, which was consistent with the research conclusions of Yan et al and Wu et al [56,57].…”
Section: Values Of Eiwb and Its Distributionsupporting
confidence: 90%
“…The "Pollution Haven Hypothesis" also proves this conclusion. This can be explained in two parts: 1) resource-based cities in China have cheap resources and immature environmental regulations, which attract foreign investment to their high energy consumption and heavypolluting industries (Yan et al, 2019) and 2) technology introduction may worsen competing domestic companies, and even crowd them out from the market (Hu and Jefferson, 2002). The competitive pressure from foreign investment has squeezed the market share of local enterprises, reducing their profits and R&D capacity.…”
Section: Basic Model Regression Resultsmentioning
confidence: 99%
“…Meanwhile, scholars have reported that multinational companies transfer pollution-intensive production to developing countries (Chung, 2014), causing serious pollution and inhibiting the green transformation of industry (Acharyya, 2009). In addition, Yan et al (2019) found the greater foreign investment a resource-based city receives, the lower its energy and technology efficiency. These results show that FDI will have a negative impact on the environment of host countries, which means that technology introduction is not conducive to industrial green transformation in the region.…”
Section: Impacts Of Technology Introduction On Industrial Green Transmentioning
confidence: 99%
“…Sustainability proposals constituted by local governments and various participants [59][60][61][62][63][64][65] demonstrate the heterogeneous aspects of urban transformative capacity. Configuring robust policies or articulating groundbreaking infrastructures may enhance the operation of urban systems and carry out sustainability goals.…”
Section: Real-time Urban Sustainability Assessment Tools In Environmementioning
confidence: 99%